Efficacy of Phenol Injection in the Management of Pilonidal Sinus Among Patients Attending Saidu Group of Teaching Hospital - Shah, Mehran; Haque, Anwar Ul (Biological and Clinical Sciences Research Journal, 2025)
Pilonidal sinus disease is an inflammatory condition characterized by a high tendency to recur. Objective: To determine the efficacy of phenol injection in treatment of pilonidal sinus in patients presenting at Saidu group of teaching hospital. Methodology: This study was carried out on 97 patients, aged 18 to 65 years with pilonidal sinus. All patients underwent phenol injection procedure under local anaesthesia, which involved sinus tract dilation of 3mm diameter, debridement, and the application of crystalline phenol. Efficacy of the treatment was assessed after 15 days of the procedure, in terms of e presence of granulation tissues, and collagen deposition. SPSS 27 was used for analyzing the gathered data. Results: The cohort in this study had a mean age 31.81 ± 14.50 years, and 54.6% male majority. The efficacy rate of the treatment was 84.5%. Efficacy demonstrated a positive significant association with younger age (p < 0.001) and urban residence (p = 0.03). Lower efficacy was observed in patients with diabetes mellitus (p < 0.001).Conclusion: Phenol injection is an effective treatment for pilonidal sinus disease, demonstrating a high efficacy rate (84.5%). Older patients, rural residents and patients with higher BMI exhibited lower efficacy rates.